Clinical Gait Evaluation with Neuromuscular Impairments (Clinical GENI) for spastic cerebral palsy - Clewes, Kylie; Dong, Yiwen; Meyer, Mary; Lowe, Evan; Schadl, Kornél; Rose, Jessica (Frontiers in Human Neuroscience, 2025)
BackgroundGait abnormalities in spastic cerebral palsy (CP) result from four primary neuromuscular impairments: muscle weakness, short muscle-relative-to-skeletal-length, muscle spasticity, and impaired selective motor control. The Clinical Gait Evaluation with Neuromuscular Impairments (Clinical GENI) was developed to help clinicians identify gait abnormalities and contributing neuromuscular impairments in spastic CP for use in any clinical setting.AimsThis study evaluated use and validity of the observational-based Clinical GENI to identify gait abnormalities and contributing neuromuscular impairments in children with spastic CP.MethodsPatients with spastic CP seen in 2023 for instrumented gait analysis and physical exam of neuromuscular impairments were evaluated using the Clinical GENI. Validity was assessed by agreement between identification of gait abnormalities on the Clinical GENI compared to 3D gait kinematics. Severity of neuromuscular impairments associated with gait abnormalities listed on the Clinical GENI was compared, and severity of neuromuscular impairment was correlated with severity of gait abnormalities.ResultsParticipants included 12 children with spastic CP (4 GMFCS I, 8 GMFCS II; mean age 11.25 years). The most common gait abnormalities were forefoot/flatfoot initial contact (IC) (16/24), flexed-knee IC (19/24), hip-flexion in single limb stance (12/24), and reduced pre-swing ankle plantarflexion (19/24). Strong agreement (83–100%) occurred between gait abnormalities on the Clinical GENI and kinematic values. Severity of neuromuscular impairment was higher (p < 0.05) for those with gait abnormalities vs. without and correlated to severity of gait abnormalities in a majority of comparisons.ConclusionResults support clinical utility and validity of the Clinical GENI for evaluating gait abnormalities and contributing neuromuscular impairments in spastic CP.